EBG antenna design - Neo, Cason Jin Sheng (2013)
This project investigates the effects of electromagnetic band gap (EBG) structures on the performance of the rectangular patch antenna. Four structures have been used, namely the mushroom-like EBG structure, the uniplanar compact EBG (UC-EBG) structure and EBG ground planes using holes and dumbbell shapes. The mushroom-like EBG and UC-EBG structures are both studied for its band gap characteristics using the dispersion diagram and the structures’ band gaps are tuned to cover the resonance frequency of 2.4 GHz. The patch was then surrounded by both structures in an effort to reduce the surface waves. The radiation patterns of the antenna surrounded by the mushroom-like EBG showed that the surface waves were suppressed effectively, leading to reduced side and back lobe levels with the energy directed to its broadside direction hence increasing its gain. However, the patch surrounded by the UC-EBGs could not exhibit the same effect despite numerous attempts to try and tune the band gap of the structure. The EBG ground plane is achieved by etching holes periodically on the ground plane beneath the patch. The band gap exhibited by the EBG ground plane is due to the satisfaction of the Bragg reflection condition. By using this property, the secondary resonance and harmonic of the antenna was able to be suppressed and the gain and efficiency showed significant improvements. The patch also showed a reduction in size. This size reduction functionality was brought forward and further enhanced with the use of dumbbell-shaped structures. Two designs of different ground plane sizes were developed and subsequently fabricated, measured and compared with the simulation results. Both patches showed a remarkable reduction in patch area of over 50%. However, due to the large cavities of the holes and dumbbell structure, the back lobe radiation of the antennas in both cases was increased by a large amount.